Pembelajaran Ekstrakulikuler Tari Untuk Meningkatkan Kepercayaan Diri Pada Siswa Tunarungu Slb Negeri Keleyan - Depi Ratnasari; Nova Estu Harsiwi (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Keleyan Bangkalan State SLB is a formal educational institution that provides services for children with special needs, one of which is the deaf. Keleyan State SLB provides extracurricular dance learning activities as one of the mandatory lessons. This research aims to (1) describe the implementation of extracurricular dance learning for deaf students at Keleyan State Special School, (2) describe the impact of implementing extracurricular dance learning for deaf students at Keleyan State Special School. This type of research uses qualitative in the form of descriptive. Data collection methods use observation, interviews and documentation. The data analysis techniques used in this research are collecting data, reducing data, presenting data, and drawing conclusions. The results of this research indicate that extracurricular dance learning activities for deaf students at Keleyan State Special School use the total method and counting techniques. In the learning process, these methods and techniques can make it easier for each student to communicate according to their respective abilities without pressure from anyone and are able to easily memorize movements through counting. Extracurricular dance learning has a positive impact in increasing the confidence of deaf students. Having a sense of self-confidence in deaf students will make them aware that deficiencies are not always an obstacle in life, deficiencies can also look special, and help deaf students blend in without feeling inferior. Dancing can also be an illustration of harmony, creativity, beauty and sensitivity to the environment.